Petroleum refining in nontechnical language - Leffler, William L. (Tulsa, Okla. : PennWell, 2008)
"William Leffler's Petroleum Refining in Nontechnical Language, 4th Edition is a comprehensive overview of key refining topics by using relevant analogies, easy-to-understand graphs, formulas, and illustrations. It is ideal for professionals who are "on the outside looking in," i.e., in any field that provides products or services to or deals with the engineers who run refineries. Each chapter was carefully written in nontechnical language giving a basic understanding of the refining industry. For further reinforcement of the material, Leffler provides exercises at the end of each chapter complete with answers." "New to this edition is important information on the nature of crude oil and raw materials and a comprehensive discussion on what sets crude oil and oil products price differentials. Also new is a chapter on lubricants as well as the latest technologies employed by refiners."--Jacket.
1. Evolution of Petroleum Refining -- 2. From the Oil Patch to the Refinery -- 3. Crude Oil Characteristics -- 4. Distilling -- 5. Vacuum Flashing -- 6. Chemistry of Petroleum -- 7. Refinery Gas Plants -- 8. Cat Cracking -- 9. Alkylation -- 10. Cat Reforming -- 11. Hydrocracking -- 12. Isomerization -- 13. Residue Reduction -- 14. Gasoline -- 15. Distillate and Residual Fuels -- 16. Hydrogen, Hydrotreating, and Sulfur Plants -- 17. Asphalt -- 18. Lubricants -- 19. Ethylene Plants -- 20. Simple and Complex Refineries -- 21. Solvent Recovery of Aromatics -- 22. Fuel Values-Heating Values -- 23. Answers to the Exercises.
Includes index.
Keywords: Petroleum -- Refining